2014
DOI: 10.1080/15321819.2013.879450
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-Lactoferrin Antibodies and Anti-Myeloperoxidase Antibodies in Autoimmune Hepatitis: A Retrospective Study

Abstract: Anti-lactoferrin antibodies (ALA) and anti-myeloperoxidase antibodies (AMPA) are specific serological markers for autoimmune hepatitis (AIH). The project aimed to detect ALA and AMPA and explore their clinical significances in AIH patients. 59 AIH patients, 217 non AIH patients, and 50 healthy controls were enrolled in this study. ALA and AMPA were detected by ELISA. Antineutropil cytoplasmic antibodies (ANCA) and anti-smooth muscle antibodies (ASMA) were examined by indirect immunofluorescence. Antimitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We found that antimicrobial proteins lysozyme and lactoferrin can, like LL37, promote TLR9 activation of B cells in complex with DNA. Interestingly, pathogenic anti-lysozyme abs have been described in Behçet's disease (28), whereas antilactoferrin abs have been described in autoimmune hepatitis (29), suggesting a mechanism of dual TLR9/BCR engagement for autoantibody induction that is similar to that described for LL37.…”
Section: Discussionmentioning
confidence: 92%
“…We found that antimicrobial proteins lysozyme and lactoferrin can, like LL37, promote TLR9 activation of B cells in complex with DNA. Interestingly, pathogenic anti-lysozyme abs have been described in Behçet's disease (28), whereas antilactoferrin abs have been described in autoimmune hepatitis (29), suggesting a mechanism of dual TLR9/BCR engagement for autoantibody induction that is similar to that described for LL37.…”
Section: Discussionmentioning
confidence: 92%
“…Autoantibodies against Lf have been documented in such pathologies as anti-neutrophil cytoplasm antibodies-associated systemic vasculitis, chronic obstructive pulmonary disease, systemic lupus erythematosus , rheumatoid arthritis, ulcerative colitis, Crohn’s disease, autoimmune hepatitis (also associated with HIV-1 infections) (Peen et al 1993 ; Dapsanse et al 2001 ; Tan et al 2014 ; Ma et al 2020 ). Interestingly, antibodies cross-reacting with Lf and myeloperoxidase were reported in renal pathology associated with formation of anti-neutrophil cytoplasm autoantibodies (Esnault et al 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…IgG antibodies are the main class of immunoglobulins involved in the fight against pathogenic microorganisms, and they participate in the secondary immune response [6,7]. Although the immune systems of newborns produce small amounts of IgM and IgA antibodies, they are unable to produce IgG antibodies-a key element of a highly precise Nutrients 2023, 15,1908 2 of 15 specific immune response [3,4]. Maternal IgG antibodies are the only ones of the five classes of immunoglobulins capable of crossing the blood-placenta barrier and entering the fetal circulatory system [7], becoming the only source of neonatal specific immunity.…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies belong to the antineutrophil cytoplasmatic auto-antibodies (ANCA)-a group of auto-antibodies against antigens contained in the cytoplasm of neutrophils-and impair the proper functioning of the immune system. Although the cause of the production of Lf-ANCA in the body has not been established so far, it is known that they underline many inflammatory and autoimmune diseases [14][15][16]. Moreover, lactoferrin deficiency has been demonstrated to be associated with recurrent infections [17,18], and the administration of lactoferrin may reduce the risk of infections of various origins [19][20][21].…”
Section: Introductionmentioning
confidence: 99%